Isótopos estáveis de C e N como indicadores da dieta da Tilápia do Nilo (Oreochromis niloticus) cultivada em tanques-rede em reservatório do semiárido brasileiro - Moraes, Cyntia Rafaela Ferreira de (Universidade Federal Rural do Semi-Árido, 2016)
This study investigated the relative contribution of natural food and commercial diets assimilated into the Nile tilapia nutrition (nilloticus niloticus) cultured in cages in the reservoir of Santa Cruz-Apodi / RN. All samples of diets and individuals were held between August and November 2013 in the reservoir cages. Individuals throughout the cultivation, as well as take in the natural food, were feed a control 40 and 32% crude protein for three stages of cultivation. For sampling isotopes dorsal muscle samples were taken from 15 individuals captured, collected food samples 15, periphyton and seston (local water filtration). All samples were dried in an oven at a temperature between 55-60 °C for a period ranging from 36-72 hours, and ground in a mortar and pestle manual to a fine powder. were performed sweeps on material samples filters. The powder samples were stored in tin capsules for conducting the analysis of stable isotopes 15N and 13C for tissue samples and diets which were performed at UC Davis Stable Isotope Laboratory Facility, University of California - USA. The field was monitored the limnological variables with the use of a multisensor. In laboratory Limnologia and Water Quality - LIMNOAQUA, analyzes were performed of growing water, in order to characterize the conditions of abiotic cages. The results of the ratios of C and N isotopes for diets and diets of fish and the contribution rates were analyzed using the R software, version 3.2.2. For data of stable isotopes of carbon and nitrogen, for samples with normal distribution and homogeneous variance was applied one-way ANOVA and Tukey test a posteriori. Where the ANOVA assumptions were not satisfied we used the nonparametric Kruskal-Wallis test and paired Wilcoxon. The values of the isotopic ratios were analyzed individually by period. Regarding the values of the contribution rates of the diets were analyzed together for each period. It was used Mixsiar Mixture Model to determine the relative contribution of diets. Limnological variables did not vary during the study period, only variations were observed for total phosphorus concentrations in the final cultivation stage and chlorophyll-a in the entire study period. Samples of feed showed significant differences in isotopic composition of 13C, and the values of 15N in tissue samples from fish between periods I and II, occurring distinct discriminating rates in diet-tissue interface for both isotopic elements of C and N in all diets. The waste feed supplied contributed to the high availability of natural foods, especially for diet based on seston.The periphyton diet (26.6%) had reduced contribution compared the diets of seston (39.2%) and fish feed (34.3%) for fish reared in Santa Cruz. In this context, it can be concluded that natural diet - seston and periphyton - (65.8%) contributed to the growth of Nile tilapia cultured in cages, changing the paradigm that only provided food is assimilated by the fish, contributing so almost exclusively on the growth of this species
Stable isotopes of C and N as dietary indicators of Nile tilapia (Oreochromis niloticus) cultivated in cages in the Brazilian semiarid region of the reservoir
Keywords: Fish; Nile tilapia - nutrition; Reservoir Santa Cruz -Apodi / RN; Cages; Stable isotopes; Peixe; Tilápia do Nilo - nutrição; Reservatório Santa Cruz -Apodi/RN; Tanques-rede; Isótopos estáveis; CIENCIAS AGRARIAS::MEDICINA VETERINARIA